Isolation and Identification of Bacterial Agents from Intramuscular Abscesses in Condemned Pig Carcasses - Arpitha, P. N.; Priya, P. M.; Niranjana, V.; Santhanalakshmi, P.; Mani, B. K.; Vasudevan, V. N. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during August, 2023 to September, 2024 at the College of Veterinary and Animal Sciences, Mannuthy, to isolate and identify bacterial agents from intramuscular abscesses in condemned pig carcasses detected during slaughter. Pus samples collected from twenty-five pigs were cultured on blood agar for bacterial isolation and the obtained isolates were identified using conventional biochemical tests along with the automated microbial identification system. Antibiotic susceptibility testing was performed and the multiple antibiotic resistance index was calculated to determine the resistance profile of each isolate. A total of twenty bacterial isolates were recovered, of which eighteen were positive on bacterial culture. Gram-positive bacteria were more prevalent than Gram-negative ones. The most frequently identified organisms were Staphylococcus spp. followed by Escherichia coli and Streptococcus spp. while less frequently isolated species included Acinetobacter lwoffii, Providencia rettgeri, Globicatella sulfidifaciens, Granulicatella adiacens, Lactobacillus species and an unidentified Gram-positive rod. Most isolates showed susceptibility to chloramphenicol, gentamicin, tetracycline, cefoperazone, levofloxacin, ofloxacin, amikacin, co-trimoxazole, ceftriaxone combined with sulbactam, amoxicillin combined with clavulanic acid and ciprofloxacin, whereas a high level of resistance was observed against penicillin G, clindamycin and methicillin. Among the twenty isolates, fifteen exhibited a multiple antibiotic resistance index greater than 0.2, indicating a multidrug-resistant profile. The emergence of multidrug-resistant bacteria highlights the growing concern of antimicrobial resistance and the findings of this study emphasise the significant role of bacterial pathogens in the formation of abscesses, ultimately contributing to carcass condemnation.